(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Background: This study examines the issue of Olympic values and doping in sport. The first aim of this pilot study was to explore athletes’ and coaches’ perceptions of the values associated with the Olympic Games and their attitudes towards doping. The second aim was to examine the relationship between the perceived Olympic values and attitudes towards doping in sport. Methods: Fifty-three athletes (mean age 19.35, SD = 4.28; 45.3% male) and 52 coaches from Uzbekistan (mean age 32.00, SD = 9.91; 46.2% male) participated in this pilot study by filling out an online survey. Results: The results showed that the value dimension ‘achievement in competition’ was most strongly associated with the Olympic Games. Participants held a more positive perception of the Olympics but were less positive towards the International Olympic Committee (IOC). The findings further revealed that the participants exhibited slightly positive attitudes towards doping in sport. However, it was found that the perceptions of values related to the Olympic Games were not related, as the attitudes towards the Olympic Games were a significant negative predictor of attitudes towards doping (β = –0.17, p < 0.05). In contrast, perceived corruption of the IOC emerged as a significant positive predictor (β = 0.62, p < 0.05). Conclusion: The study revealed a positive attitude among athletes and coaches towards the Olympic values; however, the perception of these values was not related to attitudes towards doping in sport. More significant factors in predicting attitudes towards doping were participants’ views of the Olympic Games themselves and their evaluation of the IOC as an organisation. Keywords: values, Olympic Games, International Olympic Committee, doping in sport